Instrucción a los autores: Instructions - RVE (Revista Venezolana de Enfermería, 2025)
Instructions to authors: Venezuelan Journal of Nursing (RVE) The Venezuelan Journal of Nursing (RVE) invites the scientific community to submit their original and unpublished works for publication. We are committed to upholding the highest standards of quality, originality, and ethics in every publication. General Submission Considerations All manuscripts submitted to RVE must be original and unpublished works, not previously submitted to other scientific journals. Publication is subject to rigorous criteria of thematic suitability, scientific quality, originality, timeliness, and adherence to our editorial guidelines. Manuscript Submission The author(s) must send the original manuscript to the following email addresses: revistavenezolanadeenfermeria@ucv.ve revistavenezolanaenfermeria@gmail.com